2017
DOI: 10.1002/2016jc012264
|View full text |Cite
|
Sign up to set email alerts
|

The variations of sediment transport patterns in the outerChangjiangEstuary andHangzhouBay over the last 30 years

Abstract: The research objective is to investigate the variations of sediment transport in outer Changjiang Estuary and adjacent Hangzhou Bay, induced by the decline of Changjiang River sediment discharge and massive land reclamation in the last three decades. A synchronous hydrographic survey was conducted along two transects (at the bay‐mouth and outer Changjiang Estuary, respectively) during the spring‐neap tides of January and July 2014. The results show that the suspended sediment grain size, current velocity, susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…For the case of 30.5°N, one larger counterclockwise circulation is observed. This gyre of residual sediment transport is consistent with the findings in previous studies that water and sediment “entering in the north and leaving in the south” over one tidal cycle [ Su and Wang , ; Xie et al ., , ]. For the case of 30.5°S (not shown in the figure), the residual sediment transport pattern is opposite to the case of 30.5°N.…”
Section: Model Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For the case of 30.5°N, one larger counterclockwise circulation is observed. This gyre of residual sediment transport is consistent with the findings in previous studies that water and sediment “entering in the north and leaving in the south” over one tidal cycle [ Su and Wang , ; Xie et al ., , ]. For the case of 30.5°S (not shown in the figure), the residual sediment transport pattern is opposite to the case of 30.5°N.…”
Section: Model Resultsmentioning
confidence: 98%
“…Sensitivity analysis showed that with the mean observed tidal amplitude of QE (around 1.5 m), the downslope of the modeled inside bar profile was steeper than the measured, as will be shown later. An averaged SSC of 1.0 kg/m 3 is prescribed, close to the annual average SSC at the mouth [ ECCHE et al ., ; Xie et al ., ]. Moreover, the so‐called “Thatcher‐Harleman” condition at this boundary is employed to prevent sudden SSC variations at the turning of the tide [ Van der Wegen et al ., ].…”
Section: Model Descriptionmentioning
confidence: 99%
“…When the suspended sediment plume passes the ZA, the coarse particles is filtered and fine particles may flow through the island areas, a mechanism known as the "archipelago effect" (Hu et al, 2009). Detailed analyses on the sediment budget of the Changjiang River by Wu et al, (2006), Xie et al, (2013), Yang et al, (2015) Figure 7 The distribution of mean grain size in φ (a), sorting efficient (b), and skewness (c), and sediment transport pathways of sea-bed sediment (d) in the Zhoushan Archipelago sea area (after Hu et al, 2009) and Xie et al, (2017) indicate that before the 1980s the net sediment flux across the Luchaogang, Hangzhou Bay and Zhoushan transects were 230, 135 and 85 Mt yr -1 , respectively. For the last 30 years, however, the effects of human activities, especially the building of the Three Gorges Dam in 2003, on the sediment load from Changjiang River have changed; the annual sediment discharge decreased from more than 400 Mt yr -1 before the 1980s to below 150 Mt yr -1 after 2003 (Gao and Wang, 2008;Yang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For the last 30 years, however, the effects of human activities, especially the building of the Three Gorges Dam in 2003, on the sediment load from Changjiang River have changed; the annual sediment discharge decreased from more than 400 Mt yr -1 before the 1980s to below 150 Mt yr -1 after 2003 (Gao and Wang, 2008;Yang et al, 2014). Consequently, the net sediment flux of the first two of the above mentioned three transects decreased to 186 and 122 Mt yr -1 , but that of the third one did not change much (Xie et al, 2017). Under such a condition, the sediment supply from the ZA to the adjacent sedimentary systems may become more important than that of the 1980s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation